Influence of cultivation duration on microbial taxa aggregation in Panax ginseng soils across ecological niches - Shi, Zhenting; Yang, Meling; Li, Kexin; Yang, Li; Yang, Limin (Frontiers in Microbiology, 2024)
Microbial communities are crucial for plant health and productivity. However, the influence of cultivation age on the ecological processes in assembling plant microbiomes at various ecological niches remains unclear. We selected 12 samples from ginseng farmlands with different cultivation years (N4: four years old, N6: six years old). We used soil physicochemical properties, enzyme activities, and high-throughput sequencing (16s rDNA and ITS) to examine the rhizoplane (RP), rhizosphere (RS), and bulk soil (BS). Our results indicated that cultivation years significantly affect the soil microbiome's diversity and community composition across different ecological niches. The BS microbiome experienced the largest effect, while the RS experienced the smallest. N6 showed a greater impact than N4. This effect was more pronounced on the fungal communities than the bacterial communities of various ecological niches and can be closely related to the soil's physicochemical properties. In N4 soils, we observed an upward trend in both the number of ASVs (amplicon sequence variations) and the diversity of soil microbial taxa across various ecological niches. In N4RP, the bacteria Sphingomonas, known for degrading toxic soil compounds, was present. All ecological niches in N4 showed significant enrichment of Tetracladium fungi, positively associated with crop yield (N4RP at 6.41%, N4RS at 11.31%, and N4BS at 3.45%). In N6 soils, we noted a stark decline in fungal diversity within the BS, with a 57.5% reduction in ASVs. Moreover, Sphingomonas was abundantly present in N6RS and N6BS soils. The relative abundance of the pathogen-inhibiting fungus Exophiala in N6RP and N6RS reached 34.18% and 13.71%, respectively, marking increases of 4.9-fold and 7.7-fold. Additionally, another pathogen-inhibiting fungus, Humicola, showed significant enrichment in N6BS, with a 7.5-fold increase. The phenolic acid-producing fungus Pseudogymnoascus in N6RP, N6RS, and N6BS showed increases of 2.41-fold, 2.55-fold, and 4.32-fold, respectively. We hypothesize that functional genes related to the metabolism of terpenoids and polyketides, as well as signaling molecules and interactions, regulate soil microbial taxa in ginseng from different cultivation years. In conclusion, our study enhances understanding of plant-microbe interactions and aids the sustainable development of medicinal plants, particularly by addressing ginseng succession disorder.